Genetical and physicochemical diversity among twelve Brazilian cultivars of cashew (Anacardium occidentale) - de Souza Lemos, Moaciria; do Nascimento Bordallo, Patricia; das Chagas Vidal Neto , Francisco; Nogueira Lima, Eveline; Santos Araújo Holanda, Ioná (Instituto de Ecología, A.C., 2021)
Background and Aims: Cashew (Anacardium occidentale) is a native Brazilian tree, cultivated in various warm climates across the world. The cashew kernels production has been an important economic activity for many tropical countries, providing a variety of food with great nutrition value. The genetic diversity among the early dwarf cultivars used to production is poorly understood, as is the nutritional composition among nuts from those plants. This work aimed to evaluate the physicochemical characteristics of cashew kernels and to study genetic diversity among twelve cultivars to indicate superior genotypes for future breeding programs. Methods: Cashew kernels from twelve cultivars were evaluated for pH, titratable acidity, moisture, ash, lipids and proteins. The genetic variability was assessed using RAPD and ISSR molecular markers. Data from molecular and physicochemical analyses were used to estimate the genetic distances and Mantel test approach was applied to calculate Pearson’s correlation between the data.Key results: A high genetic variability was found among the cultivars. BRS 274 and BRS 275 were the closest genetically, while CCP 09 and BRS 189 were the most distant ones. On the other hand, EMBRAPA 51 and BRS 226 showed cashew kernels with more similar physicochemical characteristics, while BRS 189 and BRS 253 had the more different ones. Moreover, no correlation was found between the physicochemical and molecular results. Cashew kernels had pH close to neutrality, low acidity, considerable moisture content, and high lipid and protein contents. Conclusions: The cashew kernels from the cultivars studied here had low acidity and pH, considerable moisture and ash contents, and high protein and lipid contents. BRS 189, BRS 253, and CCP 1001 showed the best values for proteins, lipids, acidity, and pH. In addition, those cultivars have maximum distance genetic among them, which can be used as parents in future gene combinations in breeding programs.